PEMBELAJARAN KONTEKSTUAL MELALUI INTEGRASI DIGITAL MARKETING DAN GREEN MARKETING: STRATEGI LITERASI DALAM MANAJEMEN PEMASARAN BERKELANJUTAN - Ida Bagus Separsa Kusuma; Putu Ari Utama Irawan (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
The rapid growth of digital technology and the increasing awareness of environmental issues have transformed global marketing strategies. However, the integration of digital marketing and green marketing in educational settings, particularly in the context of sustainable marketing, remains underexplored. This study aims to investigate the effect of implementing contextual-based learning through the integration of digital and green marketing on improving students literacy in sustainable marketing management. This research is a quasi-experimental study with a One-Group Pretest-Posttest design, involving 90 students as participants. Data analysis was conducted using Paired Sample T-Test. The results revealed a significant increase in the average score from the pretest (64,20) to the posttest (76,95), demonstrating a 12,75 point improvement in students' literacy. The integration of digital and green marketing in contextual learning proved effective in significantly enhancing students' understanding of sustainable marketing principles (p < 0,001). This approach contributes to bridging the gap between theory and practice, fostering students ability to apply marketing concepts in real-world sustainability contexts.